2019
DOI: 10.1016/j.eimc.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of clinical non-β-lactam-antibiotic susceptible MRSA strains: Genetic lineages and Panton-Valentine leukocidin (PVL) production

Abstract: Staphylococcus aureus resistente a meticilina (SARM) es una de las principales causas de infecciones, tanto relacionadas con la asistencia sanitaria como asociadas a la comunidad (AC). Considerando la sensibilidad a antibióticos no βlactámicos como marcador potencial de SARM-mecC y SARM-AC, el objetivo de este estudio multicéntrico fue determinar la frecuencia y líneas genéticas de cepas SARM sensibles a antibióticos no β-lactámicos (SARM-SNBL) en un estudio multicéntrico en España. Métodos:Se analizaron 45 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This CC is known to be a livestock‐lineage mostly related with ruminants but also found in wild animals, and the environment (García‐Álvarez et al ; Gómez et al ; Gómez et al ). The presence of the mecC gene in clinical isolates in Spain is still unusual, as evidenced by a recent multicentre study conducted in 12 Spanish hospitals among non‐β‐lactam‐susceptible MRSA isolates (common phenotype of mec C strains) (Ceballos et al ). Nevertheless, sporadic detections of clinical mec C MRSA strains have been reported in Spain, corresponding to the lineage t843 and ST130/ST1945 (included in CC130) (Romero‐Gómez et al ; García‐Garrote et al ; Cano‐García et al ; Benito et al ), similar to the mecC ‐MRSA isolates detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This CC is known to be a livestock‐lineage mostly related with ruminants but also found in wild animals, and the environment (García‐Álvarez et al ; Gómez et al ; Gómez et al ). The presence of the mecC gene in clinical isolates in Spain is still unusual, as evidenced by a recent multicentre study conducted in 12 Spanish hospitals among non‐β‐lactam‐susceptible MRSA isolates (common phenotype of mec C strains) (Ceballos et al ). Nevertheless, sporadic detections of clinical mec C MRSA strains have been reported in Spain, corresponding to the lineage t843 and ST130/ST1945 (included in CC130) (Romero‐Gómez et al ; García‐Garrote et al ; Cano‐García et al ; Benito et al ), similar to the mecC ‐MRSA isolates detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…While all S. aureus isolates were collected in some studies [ 29 , 38 , 45 ], only MRSA isolates were included in others [ 24 , 26 , 27 , 28 , 32 , 33 , 36 , 41 , 42 ]. Moreover, several studies were more restrictive and only used isolates that showed characteristics suspected of carrying the mecC gene such as spa types associated with mecC -positive clonal lineages previously described, mecA -negative MRSA isolates, isolates with antimicrobial susceptibility suspected to be mecC -positive or pvl -negative MRSA isolates [ 25 , 26 , 37 , 69 ] ( Table S1 ). In any case, the mecC -MRSA human prevalence detected in most of the studies was very low.…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…In any case, the mecC -MRSA human prevalence detected in most of the studies was very low. Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ].…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
See 1 more Smart Citation